Comparison of level of awareness regarding eye donation among medical, engineering and law students in Jammu, India - Manhas, Angli; Manhas, Rameshwar S.; Manhas, Gaurav S.; Gupta, Dinesh; Kumar, Dinesh (International Journal of Research in Medical Sciences, 2018)
Background: Blindness due to cornea is a major public health issue, especially in developing countries like India. Corneal transplantation is the treatment for restoring vision in corneal blind patients. The aim of present study was to compare the level of awareness regarding eye donation among medical, engineering and law students. Methods: The present cross sectional, comparative study involved students following their respective courses (1st final year) from October 2017 to December 2017. Out of 168 students, 60 were medical, 56 were engineering and 52 were law students. The study started with initial clarification of questions and those who were willing to participate, were requested to fill the semi-structure pilot tested questionnaire form on eye donation with informed consent. Results: All the students were aware of eye donation, but medical students were much aware on various parameters. The most powerful information tool to reach out all the students was television whereas among medical ophthalmology is one of subject they study in their respective course which provide them maximum knowledge regarding eye donation. Conclusions: Level of awareness and knowledge regarding eye donation is much better among medical students (MBBS) in comparison with engineering and law students. Thus, professionals (medical doctors, engineers and lawyers) should be actively involved in creating awareness regarding eye donation and hence play vital role to reach out people for optimum benefit.